Optimization of physical rehabilitation in congenital clubfoot - M.L. Golovakha (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The aim of the study was to improve the results of treatment of children with typical form of congenital clubfoot by optimizing of physical rehabilitation. The study included the following objectives: to make the algorithm work with the child, to justify the basis of physical rehabilitation, to study its effects, to develop a framework of implementation and optimization of the physical rehabilitation of children with congenital clubfoot. In the course of the study were 62 children involved with the typical form of congenital clubfoot: the main group (n = 42) and control group (n = 42). Age children from 4 years to 7 years. Physical rehabilitation was a logical continuation of treatment. Optimization analysis was performed by clinical examination, radiometric data and indicators of functional methods of research. Comparative analysis of the results of the physical rehabilitation of children with congenital clubfoot in both groups showed a trend more pronounced positive changes in children the main group in all respects.